Feasibility study on information services business - Ang, Chwee Peng (2009)
Information is becoming a crucial resource as companies compete in the global arena and where companies thrive or die with changes in the market environment. Information Providers can play a value-added role by supplying companies with pertinent business information in electronic or digital forms. The ability of these information providers to meet the needs of information users is governed by the limit of understanding the information seeking pattern of users and their information requirements. The research findings in this paper provide clues on the usage of the various types of business information, the current source/media used, and the information requirements measured along seven defined information characteristics. It also draws attention to the various influencing factors: organizational, personal, and functional activities; on the information requirements and usage pattern. This research also gathers results on the awareness of information providers services; and satisfaction levels of current users of such electronic information providers. The current users' satisfaction is measured along the same seven information characteristics that are used to measure the users information requirements. The nature of this research should be considered exploratory. Nevertheless it serves a practical purpose for anyone in the business of providing business information as the results would be useful for developing and marketing new and unique information product/service so as to gain a competitive advantage.